2019
DOI: 10.1002/admi.201900938
|View full text |Cite
|
Sign up to set email alerts
|

On the Self‐Repair of WS2/a‐C Tribocoating

Abstract: This study investigates the self‐healing capacity of a WS2/amorphous carbon (a‐C) tribocoating. It is found that prenotches up to 45 µm wide in the WS2/a‐C coating surface can be completely healed under the stimulus of sliding operations. The in situ tribotest of 100, 500, 2000, and 6000 laps confirms a dynamic filling of tribofilms that patch the voids and prenotched damages. The stabilized coefficient of friction (CoF) remains at an ultralow value down to 0.02, independent of the prenotched damage at the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…008-0237), indicating that the WS 2 layers are slightly expanded. 33 Note that such thick, long-range, almost fully well-aligned WS 2 platelets have rarely been reported in earlier studies, 5 , 34 where most often only a few nanometer thick layers of such platelets were observed. In addition, previous studies 35 , 36 suggested that amorphous TMDC platelets gradually crystallize from the bottom of the wear track and only become fully crystalline in the outmost part of the tribofilm in direct contact with the counterpart; in other words, these works describe a gradient of crystallinity in the layer, from amorphous to crystalline.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…008-0237), indicating that the WS 2 layers are slightly expanded. 33 Note that such thick, long-range, almost fully well-aligned WS 2 platelets have rarely been reported in earlier studies, 5 , 34 where most often only a few nanometer thick layers of such platelets were observed. In addition, previous studies 35 , 36 suggested that amorphous TMDC platelets gradually crystallize from the bottom of the wear track and only become fully crystalline in the outmost part of the tribofilm in direct contact with the counterpart; in other words, these works describe a gradient of crystallinity in the layer, from amorphous to crystalline.…”
Section: Discussionmentioning
confidence: 82%
“…Note that sulfur content and S/M (M = W, Mo) ratios have been identified as crucial factors in TMDC-based coatings to enable the formation of enough lubricous phases for a favorable tribological behavior. 33 , 48 Stable ultralow CoFs of 0.02 have been observed in the range S/W = 1.33–1.79. 29 According to Table 1 , the as-deposited coating and the one annealed at 200 °C have a S/W ratio of 1.30.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations